2011
DOI: 10.1111/j.1365-313x.2011.04488.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Arabidopsis salt acclimation induced by up‐regulation of HY1 and the regulatory role of RbohD‐derived reactive oxygen species synthesis

Abstract: SUMMARYIn Arabidopsis thaliana, a family of four genes (HY1, HO2, HO3 and HO4) encode haem oxygenase (HO), and play a major role in phytochrome chromophore biosynthesis. To characterize the contribution of the various haem oxygenase isoforms involved in salt acclimation, the effects of NaCl on seed germination and primary root growth in Arabidopsis wild-type and four HO mutants (hy1-100, ho2, ho3 and ho4) were compared. Among the four HO mutants, hy1-100 displayed maximal sensitivity to salinity and showed no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
211
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(222 citation statements)
references
References 64 publications
11
211
0
Order By: Relevance
“…This can be achieved by either seed priming, or by direct irrigation of plants prior high dose 14 salt stress (Patade et al, 2009;Xie et al, 2011). In the present work in order to determine the effectiveness of salt acclimation young wheat plants were trained with low concentration of NaCl before irrigation with high salinity and the acclimation mechanisms were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…This can be achieved by either seed priming, or by direct irrigation of plants prior high dose 14 salt stress (Patade et al, 2009;Xie et al, 2011). In the present work in order to determine the effectiveness of salt acclimation young wheat plants were trained with low concentration of NaCl before irrigation with high salinity and the acclimation mechanisms were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in plants demonstrated that HO contributes to alleviating the effects of salt stress. These studies found that the activity of HO was induced due to oxidative stress under salinity conditions (Zilli et al, 2008(Zilli et al, , 2009Xie et al, 2008Xie et al, , 2011Wei et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Previously, it was reported that treatment of potato (Solanum tuberosum) tubers with hyphal wall components from Phytophthora infestans causes a rapid and transient accumulation of H 2 O 2 at 1 h (phase I), followed by a massive oxidative burst at 6 to 9 h (phase II; Kobayashi et al, 2007). Similarly, biphasic ROS production was recently observed in plants subjected to other stresses such as ozone and H 2 O 2 (Xie et al, 2011). Despite these results, detailed studies on biphasic ROS production have not been performed.…”
mentioning
confidence: 99%